A cross-disciplinary approach to minimising the risks of maritime transport in the Gulf of Finland. (29th May 2009) - Klemola, Eveliina; Kuronen, Jenni; Kalli, Juha; Arola, Tommi; Hanninen, Maria; Lehikoinen, Annukka; Kuikka, Sakari; Kujala, Pentti; Tapaninen, Ulla
The maritime traffic in the Gulf of Finland is predicted to rapidly increase in the near future, which increases the environmental risks both through direct environmental effects and by increasing the accident risk. This paper describes a multidisciplinary modelling approach, where, based on growth predictions, the maritime traffic in the Gulf of Finland in the year 2015 is modelled and the accident risk, the direct environmental effects and the risk of environmental accidents are evaluated. Finally, the effects of national and international legislation and other management actions are modelled, to produce advice and support for governmental decision makers. In the modelling work, Bayesian Networks (BNs) are applied. The approach produces unique information on the accident risks and their effects separately for each marine route used, which enables efficient local risk control actions to be taken by the decision makers to decrease the probability of accidents.